2011
DOI: 10.1007/12_2011_119
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Chitosan Nanoparticles for Tumor Imaging and Therapy

Abstract: Chitosan and its derivatives have been widely used for various biomedical applications because of their unique chemical and biological characters. The amine groups in the backbone of chitosan allow chemical modification to change the physical properties of chitosan. Based on hydrophobic or charge interactions with this chitosan polymer backbone, stable self-assembled nanoparticles can be fabricated in aqueous condition. These nanosized structures enable intravenous injection and show large accumulation in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 88 publications
0
10
1
Order By: Relevance
“…However, the use of MTX is limited due to its poor solubility, non-specific drug delivery and toxic side effects, which leads to disruption of the anticancer treatment for the patient [7]. Nanocarriers, as chemotherapeutic agents, offer novel strategies (i.e., liposomes, polymeric and inorganic nanoparticles, micelles, dendrimers and carbon nanotubes) for targeting cancer cells and tumor zones without causing major damage to the surrounding healthy tissue, and hence, they allow the chemotherapeutic agent to accumulate in tumor zones due to their enhanced permeation and retention effect [8,9]. Chitosan (CH) is a non-toxic, biocompatible, biodegradable, and adsorptive polymer with proven anticancer activity against different cancer cell lines due to disruption of the G1/S phases of the cell cycle and its ability to increase TUNEL-positive cells, which is accompanied by a subtle increase in caspase activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of MTX is limited due to its poor solubility, non-specific drug delivery and toxic side effects, which leads to disruption of the anticancer treatment for the patient [7]. Nanocarriers, as chemotherapeutic agents, offer novel strategies (i.e., liposomes, polymeric and inorganic nanoparticles, micelles, dendrimers and carbon nanotubes) for targeting cancer cells and tumor zones without causing major damage to the surrounding healthy tissue, and hence, they allow the chemotherapeutic agent to accumulate in tumor zones due to their enhanced permeation and retention effect [8,9]. Chitosan (CH) is a non-toxic, biocompatible, biodegradable, and adsorptive polymer with proven anticancer activity against different cancer cell lines due to disruption of the G1/S phases of the cell cycle and its ability to increase TUNEL-positive cells, which is accompanied by a subtle increase in caspase activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al showed that the prolonged blood circulation of the chitosan-based NPs induced higher EPR efficiency of the NPs [78]. Yhee described that particle size, particle shape, and surface charge of NPs also affected their blood circulation time and EPR effect [79].…”
Section: Targeting Strategies Of Drug-loaded Npsmentioning
confidence: 99%
“…Recently, there have been many research activities on bio-robots to embody various living organisms' mechanisms by combining biomaterials, such as living cells, with soft materials that are flexible but have sufficient strength. The most important factor here is the binding force between the biomaterial used and the soft material [11]. Hydrogels are one of the materials that can best imitate such properties.…”
Section: Designing 4d Mask Pack Using Hydrogelsmentioning
confidence: 99%